Peningkatan Tata Kelola Ti Dengan Cobit 5 di Perguruan Tinggi: Studi Kasus Universitas Stikubank Semarang - Nugroho, Isworo; Khristianto, Teguh; Mariana, Novita; Utomo, Agus Prasetyo (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
This research examines the implementation of the COBIT 5 Domain DSS (Deliver, Support, andService) framework in enhancing Information Technology (IT) governance in the higher education context,with a specific focus on Stikubank University in Semarang. Findings from surveys and interviews conductedwith university stakeholders revealed varying levels of understanding of COBIT 5, challenges in itsutilization, and issues related to IT performance measurement. Recommendations include the developmentof intensive training programs, improvements in IT performance measurement, enhanced IT service support,and initiatives to transform the organizational culture. This study provides valuable insights for other highereducation institutions striving to enhance their IT governance through the utilization of the COBIT 5Framework.